Selection of Staphylococcus aureus in a murine nasopharyngeal colonization model - Salgado, Breno A. B.; Waters, Elaine M.; Moran, Josephine C.; Kadioglu, Aras; Horsburgh, Malcolm J. (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococcus aureus nasal colonization is a risk factor for infection. A large proportion of the population are identified as potential S. aureus carriers yet we only partially understand the repertoire of genetic factors that promote long-term nasal colonization. Here we present a murine model of nasopharyngeal colonization that requires a low S. aureus inoculum and is amenable to experimental evolution approaches. We used this model to experimentally evolve S. aureus using successive passages in the nasopharynx to identify those genetic loci under selection. After 3 cycles of colonization, mutations were identified in mannitol, sorbitol, arginine, nitrite and lactate metabolism genes promoting key pathways in nasal colonization. Stress responses were identified as being under selective pressure, with mutations in DNA repair genes including dnaJ and recF and key stress response genes clpL, rpoB and ahpF. Peptidoglycan synthesis pathway genes also revealed mutations indicating potential selection for alteration of the cell surface. The murine model used here is versatile to question colonization, persistence and evolution studies. We studied the human pathogen Staphylococcus aureus in our search to determine factors that contribute to its ability to live in the human nose and throat. The anterior nares and nasopharynx are considered primary habitats but we do not understand how the pathogen adapts as it moves from one person to the next. We first determined sustained survival of the pathogen over multiple days in the nasopharynx that might act as a good model for human persistence due to the low numbers of bacteria needed for it to establish. By using successive rounds of colonization of the nasopharynx across different mice we revealed that multiple genetic changes in the S. aureus occurred. These changes were found in genes associated with the cell surface and metabolism and might indicate adaptation to the niche. One gene showed an accumulation of multiple mutations supporting a key contribution in adaptation but the role of the protein it encodes is not yet known. The contribution of these genes and genetic changes are unclear but indicate an area for future research to better understand how this common human pathogen is so successful at human colonization and survival.